DEVELOPING MATHMATICS PROBLEMS OF LITERACY NUMERACY BASED OF LOCAL WISDOM CONTEXT OF MALUKU - Paunno, Destalia; Laamena, Christina M; Moma, La (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2024)
One of the skills required in learning mathematics is numerical literacy. In learning mathematics, numeration literacy requires students to be able to solve contextual problems in everyday life. Students' literacy and numeration skills are generally low. One of the reasons is the lack of literacy training in numeration, which is usually routine issues that do not sharpen students' literacy and numeration skills. The lack of use of cultural contexts in learning and in matters also makes students more likely not to want to improve their literacy and numeration skills. This research is a developmental research aimed at developing the issue of numeration literacy based on the local wisdom of Maluku by expressing how the process of development and how the numerational literacy ability of students in solving the issue is numeration based on local Wisdom developed. The development model used is the development model by Tessmer.Tessmer's development consists of several stages: preliminary, self-evaluation, prototyping (self evaluation, one-toone, and small group) and field testing. The instrument in this research is to raise the practicality of matters and matters of numeration literacy based on local wisdom developed. The result or product of this study is eight elements of local wisdom-based numeration literacy, consisting of three True-False complex double-choice questions, one deceptive question and four descriptive questions